Problem Solving To Reduce Long-Term Idle Well in Oil Field Using Kepner-Tregoe Approach (The Indonesian Journal of Business Administration, 2015)
Abstract. The oil and gas industry brings many economic benefits. However, these benefits are not without consequences. Oil and gas exploration could have a detrimental effect on the environment, over the time some of wells were shut in due to poor economics or because of mechanical problem, making them poor candidates for future use. There has been a steady increase in long-term idle wells that potentially has negative environmental impacts in one of the biggest oil field in Indonesia. To address the increasing number of long-term idle wells in this field, the division of production operation develops strategies to reduce the idle well inventory and lower the State’s potential well plugging liability in the future. This process resulted in the development of new strategies that require additional commitment for financial and resources in addition, idle well assessment is required to protect freshwater and hydrocarbon resources, and to help determine a well’s future resource potential. Kepner-Tregoe (K.T.) method was used to analyze what is the main and real issue cause huge number of long-term idle wells in Delta field. Methodology develops based on identified root cause, and then groups each root problem based on possible solution. Using this method, it is known that the majority of huge numbers of long-term idle well wells caused by (1) lack of Long term Plan, (2) low resources limitation, (3) limited alternative technology, (4) compete with other job, (5) lack of management commitment. Problems identified by Kepner-Tregoe using Method (KT) will be solve with two main activities; Negotiation of resources (business negotiations) to the company management to support plug and abandonment project, while for new alternative technologies, which is 1 sidetrack projects, will using project management processes to evaluate the feasibility of the project.With two major initiatives above, this company can avoid sanction ~250 MM USD abandonment job and make revenue ~ 2.1 MM USD from sidetrack project. Program Goals: (1) Reduce idle well inventory with the emphasis on long-term idle wells, (2) Reduce well plugging liability in the future, (4) secure resource to perform well abandonment, (4) re-active well with potential remaining reserveKey words: Kepner-Tregoe, Decision Analysis, Problem Solving, Project Management